(3aJM GdhMjO aj TQM GdbUjOs - (3Ydj Hf eMeO GdSNGhis; (3GdbGSe Hf ajQg Hf Nda Hf CMeO GdQYjfj, CHh eMeO GdTGWHj,J (B590 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ybd cJGHg GdYRjR fhQkG dci fgJOi Hg s
(3BNQgG (B:s
(3SjOfG eMeO hBdg Sde JSdjekG cKjQkG WjHkG hMSHfG Gddg hfYe Gdhcjd s
(3YOO ChQGb GdLRA GdChd (B257 (3UaMI hGdKGfi (B413 (3UaMIs
(3fSNI KGfjIs
(3gPG GdeNWhW bjes
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs